A Suplementação de isoflavona não potencializa os efeitos do exercício físico na redução da pressão arterial e sintomatologia climatérica: ensaio clínico, controlado, randomizado e duplo cego. - Costa, Juliene Gonçalves (2017)
Introduction: Several endocrine and metabolic changes occur during the climacteric period from the deficit in estrogen production, through the aging process and lifestyle, which result in the appearance of climatic symptoms and an increased risk of cardiovascular diseases. Isoflavone supplementation along with exercise are alternatives used to reverse and/or delay these characteristic changes from the postmenopausal period. Objectives: To verify if supplementation of 100mg of isoflavone combined with combined exercise has additive effects on ambulatory blood pressure responses and on climacteric symptoms in normotensive postmenopausal women. Materials and Methods: A randomized, double-blind, controlled clinical trial involving 32 postmenopausal women, aged 54.4±5.4 years, BMI of 26.6±3.0 kg/m2 and 5.6±4.6 years after menopause randomly assigned to the group: placebo and exercise (PLA+EXE, n=15) or 100mg of isoflavone and exercise (ISO+EXE, n=17). Before and after 10 weeks the climacteric symptoms were evaluated by three specific questionnaires: Kupperman-Blatt Index (IKB), Menopause Rating Scale (MRS) and Cervantes Scale (EC) and blood pressure through ambulatory blood pressure monitoring for 24 hours. To verify the correlation between the questionnaires we used the Sperman Correlation, and the analysis of the symptomatology and the blood pressure of the periods of wakefulness, sleep, 24 hours and AUC, between the groups was used ANCOVA with the covariate adjusted by the value of the pre . The analysis of Generalized Estimates (GEE) with multiple comparisons made with the Bonferroni correction, used to evaluate before and after intervention at intervals every 2 hours, using SPSS software version 23. The variation blood pressure over time was analyzed by the area under the curve (AUC) by the trapezoidal method in the software GraphPad Prisma version 6. The significance level adopted was p<0.05. Results: ANCOVA showed a reduction in the climacteric symptomatology in the two groups, in the total score and in the domains, but with no difference between the groups. The reductions were 45% and 50% in the Kuppermam-Blatt index, 41% and 52% in the MRS, 39% and 39% CE, in the ISO+EXE and PLA+EXE groups, respectively. In the descriptive analysis of the Kupperman-Blatt Index values there was an increase in the absence of symptoms from 48% to 77% in the ISO+EXE group and 24% to 58% in the PLA+EXE group. In the blood pressure values there was no difference between the groups in the mean and AUC values of SBP, DBP and MAP in the wake, sleep and total 24 hour periods. However, the comparison of the 2-hour points by the GEE showed a reduction of the post compared with the PAD (0, 2 and 12 hours), MAP (0 and 24 hours) in the PLA+EXE group, and the ISO+EXE group only in the time in SBP. Conclusion: Supplementation of soy isoflavone at a dose of 100 mg/day does not enhance the effects of training on the reduction of climacteric symptoms and ambulatory blood pressure in normotensive postmenopausal women.